Diseño arquitectónico de un Centro Gerontológico implementando arquitectura sensorial en la ciudad de Babahoyo - Castro León, Fabrizzio Duberly (2024)
The project proposes a Gerontological Center for the city of Babahoyo, aimed at the development of the city with adequate public facilities to meet the current demand and future projections. The design merges and provides comprehensive care for the elderly, improving their quality of life in accordance with universal human rights. It is realized through a representation that includes regulatory standards, universal design, and sensory architecture. Its composition consists of a mix of outdoor spaces with components such as rest areas, recreation, administrative areas, and other complementary spaces that meet the demand for spacious, friendly, and adaptable areas, allowing free, fluid, and inclusive mobility so that they can carry out their activities in safe spaces and generate independence despite any limitations that may exist....